3D-Multiple Object Tracking training task improves passing decision-making accuracy in soccer players - Romeas, T.; Guldner, A.; Faubert, J. (Psychology of Sport and Exercise, 2015)
• Soccer players were trained using a 3D-MOT perceptual-cognitive training task, • On-field transferability of the training on decision-making was assessed, • On-field passing decision-making improved after the 3D-MOT training, • Players' decision confidence improved proportionally in the 3D-MOT group • 3D-MOT is the first non-sport specific training task to transfer onto the field in athletes Objectives: The ability to perform a context-free 3-dimensional multiple object tracking (3D-MOT) task has been highly related to athletic performance. In the present study, we assessed the transferability of a perceptual-cognitive 3D-MOT training from a laboratory setting to a soccer field, a sport in which the capacity to correctly read the dynamic visual scene is a prerequisite to performance. Design: Throughout pre- and post-training sessions, we looked at three essential skills (passing, dribbling, shooting) that are used to gain the upper hand over the opponent. Method: We recorded decision-making accuracy during small-sided games in university-level soccer players (n = 23) before and after a training protocol. Experimental (n = 9) and active control (n = 7) groups were respectively trained during 10 sessions of 3D-MOT or 3D soccer videos. A passive control group (n = 7) did not received any particular training or instructions. Results: Decision-making accuracy in passing, but not in dribbling and shooting, between pre- and post-sessions was superior for the 3D-MOT trained group compared to control groups. This result was correlated with the players' subjective decision-making accuracy, rated after pre- and post-sessions through a visual analogue scale questionnaire. Conclusions: To our knowledge, this study represents the first evidence in which a non-contextual, perceptual-cognitive training exercise has a transfer effect onto the field in athletes.